Konsep Pembinaan Karakter Anak Menurut Abdul Malik Fadjar - Muhammad Saddam (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
Abdul Malik Fadjar is one of the leaders of Indonesian education who has provided many services and thoughts in Islamic education and character education. Apart from being the implementer of education, Malik Fadjar is also a policy maker in the field of education. This study aims to examine Abdul Malik Fadjar's thoughts on children's character building, to explore Abdul Malik Fadjar's policies in the field of character building, and to find out strategies for implementing Abdul Malik Fadjar's thoughts in building children's character. This research is a type of library research with data analysis techniques in this study using the method of content analysis (content analysis). The results show that according to Malik's character, there are two dimensions of human life that must be done well, namely the divine dimension (with Islamic values, faith, ihsan and taqwa), and the Human dimension (with the values ​​of friendship, brotherhood, equality and kindness). thought). The method of character building according to Malik is a method of exemplary, habituation and da'wah methods. Malik's thoughts are modernist-religious and according to the flow of educational philosophy, it is included in the convergence flow. The strategy for implementing Malik's character development in character building is to apply additional hours in learning Islamic religious education in schools. The policies that Malik Fadjar has implemented are: integrating religion and other disciplines, revising the CBSA curriculum to become KBK, removing Ebtanas at the SD/MI level and revising the Education System Law to become the National Education System Law.